A Portrait of Andreas Bodenstein von Karlstadt by Lucas Cranach the Elder. Issue 3 (1st September 2020) - Zorzin, Alejandro
ABSTRACT: The traditional facial portrait of Andreas Bodenstein von Karlstadt has significantly influenced his reception. His apparently sole authentic image was not known until 1988. It is a small woodcut on a broadsheet printed in commemoration of his death in Basel (1541). Previously, the notion was widespread that he was of a swarthy, (almost) negroid (nigricans) appearance. However, there is a double portrait, dated 1522, by Lucas Cranach the Elder, of an anonymous man and bride, and known to the scholarly world since the 1920s. A comparison of the features of the 1541 Basel portrait with those of the unknown man on the Cranach painting indicates that they quite possibly depict the same person. Since Karlstadt's wedding with Anna von Mochau took place on 19 January 1522, there are strong reasons to surmise that the these Cranach portraitures were made for the private possession of the Reformer and his wife.